A Diarylethene‐Based Photoswitch and its Photomodulation of the Fluorescence of Conjugated Polymers. Issue 67 (7th November 2018) - Liu, Ronghua; Yang, Yu; Cui, Qianling; Xu, Wenqiang; Peng, Rui; Li, Lidong
Abstract: Photochromic diarylethene derivatives, which can reversibly switch the fluorescence of adjacent fluorophores between the ON and OFF states under light irradiation, have been widely used to construct photoswitchable materials. Herein, eight dithienylethene (DTE) groups are integrated onto one polyhedral oligomeric silsesquioxane (POSS) core, obtaining a novel super molecular photoswitch. After being doped into conjugated polymer nanoparticles, the POSS‐DTE8 molecules show a higher contrast on/off photoswitching performance and a quicker responsive speed than free DTE molecules at same molar concentration of photochromic units. This enhanced photoswitching efficiency is attributed to the increased molecular interaction of the ring‐open form and lowered energy of the ring‐closed form of the DTE units on the POSS core, which is beneficial for the ring‐closing reaction and subsequent energy transfer between photoswitch and fluorophores. In addition, POSS‐DTE8 also exhibits good photomodulation behavior in the conjugated polymer film, giving it potential applications in optical devices. Abstract : Switch it up ! A photoswitching molecule, POSS‐DTE8, was synthesized with eight dithienylethene (DTE) units integrated onto a polyhedral oligomeric silsesquioxane (POSS) core. Upon being doped into conjugated polymer nanoparticles with a low doping content (10 %), POSS‐DTE8 exhibits a much higher fluorescence contrast by photochemically modulating the emission compared with free DTE molecules with the same number of photochromic units (see figure).